2014
DOI: 10.5835/jecm.omu.30.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Mean platelet volume in diagnosis of gestational diabetes

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
2
0
0
Order By: Relevance
“…6 There was no association of plateletcrit with GDM patients in the study and similar results were also observed by Erikçi et al whereas Ahmet et al noted it to be slightly higher in patients with GDM. There was no association between platelet distribution width and GDM and similar results were elicited by Muhammet et al and Erikçi et al 4,7 In the study, no significant association was found between Hemoglobin and Hematocrit values with GDM and similar findings have been reported by Erikçi et al and Çelikel et al 4,8 On performing Spearman's regression analysis, there was a positive correlation between mean platelet volume and the value of glucose challenge test in the present study which has not been reported in previous studies. An inverse correlation between platelet count and value of glucose challenge test was also noted.…”
Section: Discussionsupporting
confidence: 87%
“…6 There was no association of plateletcrit with GDM patients in the study and similar results were also observed by Erikçi et al whereas Ahmet et al noted it to be slightly higher in patients with GDM. There was no association between platelet distribution width and GDM and similar results were elicited by Muhammet et al and Erikçi et al 4,7 In the study, no significant association was found between Hemoglobin and Hematocrit values with GDM and similar findings have been reported by Erikçi et al and Çelikel et al 4,8 On performing Spearman's regression analysis, there was a positive correlation between mean platelet volume and the value of glucose challenge test in the present study which has not been reported in previous studies. An inverse correlation between platelet count and value of glucose challenge test was also noted.…”
Section: Discussionsupporting
confidence: 87%
“…Lower MPV values in GDM patients as compared to healthy women were the most important finding of our study, especially in light of the fact that in most previous studies MPV values in GDM patients values were either higher (17,19,20), or the same as in healthy controls (16). Currently, the MPV test is not regarded as a marker of platelet function because of the test results may be affected by the following factors: time from obtaining the specimen until the analysis, the use of anticoagulated tubes, and the lack of a standardized method of measurement (21,22).…”
Section: Discussionsupporting
confidence: 64%